KONSTRUKSI MAKNA TERSEMBUNYI DALAM LIRIK DJ VIRAL: KAJIAN PRAGMATIK-KOGNITIF PADA PLATFORM VIDEO PENDEK - Muhammad Ramdhan Fathin Al Farabi; Mei Fatmila Sari; Andriansyah; Aditya Pratama; Septia Uswatun Hasanah (Jurusan Pendidikan Bahasa dan Seni Fakultas Keguruan dan Ilmu Pendidikan Universitas Lampung, 2026)
Lyrics containing sexual, drug-related, and violent content are widely consumed by teenagers as background music for dancing and memes without adequate semantic understanding. This study aims to analyze the pragmatic-cognitive mechanisms at work in the consumption of such problematic lyrics, using four viral songs as case studies. The method used is a qualitative pragmatic-cognitive analysis based on Relevance Theory, cognitive schema theory, and media cultivation theory. The analysis focuses on identifying illocutionary acts, conversational implicatures, presuppositions, and mapping the patterns of adolescents’ cognitive processing. The research findings reveal two dominant cognitive patterns: the “Ignorant Pattern,” in which adolescents consume lyrics without decoding problematic meanings due to a lack of relevant cognitive schemas; and the “Deliberate Framing Pattern,” in which adolescents are aware of the problematic meanings but reframe them within a context of humor or social irony. This study introduces the concept of an “algorithmic vacuum of meaning.” These findings extend media cultivation theory to the context of fragmented algorithmic consumption and provide a foundation for the development of a differential media literacy model for short-form video platforms. Lirik bermuatan seksual, narkoba, dan kekerasan dikonsumsi secara masif oleh remaja sebagai backsound tarian dan meme tanpa pemahaman semantik yang memadai. Penelitian ini bertujuan menganalisis mekanisme pragmatik-kognitif yang bekerja dalam proses konsumsi lirik bermasalah tersebut, dengan studi kasus empat lagu viral. Metode yang digunakan adalah analisis pragmatik-kognitif kualitatif berbasis Relevance Theory, teori skema kognitif, dan teori kultivasi media. Analisis difokuskan pada identifikasi tindak tutur ilokusioner, implikatur konversasional, presuposisi, serta pemetaan pola pemrosesan kognitif remaja. Hasil penelitian mengungkap dua pola kognitif dominan: Pola Ignorant, di mana remaja mengonsumsi lirik tanpa mendekode makna bermasalah karena minimnya skema kognitif yang relevan; serta Pola Deliberate Framing, di mana remaja menyadari makna bermasalah namun mengemas ulangnya dalam bingkai humor atau ironi sosial. Penelitian ini memperkenalkan konsep vacuum of meaning algoritmik. Temuan ini memperluas teori kultivasi media ke konteks konsumsi algoritmik terfragmentasi dan memberikan landasan bagi pengembangan model literasi media yang diferensial untuk platform video pendek.